1995
DOI: 10.1071/ar9951189
|View full text |Cite
|
Sign up to set email alerts
|

Responses in wool growth, liveweight, glutathione and amino acids, in Merino wethers fed increasing amounts of methionine protected from degradation in the rumen

Abstract: The aim of the experiments reported was to evaluate the protection from microbial breakdown of two methionine formulations (Lactet and Mepron) and to measure responses in wool production, liveweight, amino acids and glutathione in blood and tissues when one of these forms of methionine (Lactet) was supplied to merino wethers fed at maintenance. Lactet was well protected against microbial breakdown in the rumen. Peak values for concentrations of methionine in plasma, following administration of the different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…According to published reports of responses to dietary supplementation with rumenprotected methionine (Lactet 1 ), 0.6 g of methionine should increase wool growth by between about 3 and 7%. 8,9,13 Similar responses have been reported when methionine has been administered via the abomasum. 27,28 The observed responses in wool growth (8%) and live weight gain (7%) in the current experiment are consistent with almost all the extra methionine in the transgenic lupin seed being protected.…”
Section: Discussionsupporting
confidence: 66%
“…According to published reports of responses to dietary supplementation with rumenprotected methionine (Lactet 1 ), 0.6 g of methionine should increase wool growth by between about 3 and 7%. 8,9,13 Similar responses have been reported when methionine has been administered via the abomasum. 27,28 The observed responses in wool growth (8%) and live weight gain (7%) in the current experiment are consistent with almost all the extra methionine in the transgenic lupin seed being protected.…”
Section: Discussionsupporting
confidence: 66%
“…The supply of essential amino acids relative to total energy supply influences the absolute and relative rate of protein and fat accretion in lambs. It is well documented that methionine and cysteine are the primary limiting amino acids for wool production and both wool production and live weight gain can be improved by supplementing sheep with methionine [43]. Gaillard et al [9] showed that most of the seaweeds investigated (Porphyra incl.)…”
Section: In Vivomentioning
confidence: 99%
“…This result concluded that haylage could increase palatability causing an increment in feed intake and in turn, increasing in amino acids. It is well known that Methionine amino acid increased the efficiency of conversion of metabolisable protein to wool and in turn increased wool production (Mata et al 1995). However, Ward (1998) found that wool contains higher concentrations of serine and Arginine, as well as Cysteine.…”
Section: Salt Tolerant Plants and Fiber Amino Acids Contentesmentioning
confidence: 99%
“…Methionine has been shown to cause rapid increases in fiber growth (Sahoo and Soren, 2011). Provision of protected methionine to adult withers fed to maintenance increased the efficiency of conversion of metabolisable protein to wool from 12.3% to 17.2%, and increased wool production from 9.6 to 13.5 g/d (Mata et al, 1995). On the other hand, Imik and Gunlu (2011) have found that the elasticity, length and diameter of wool fibers have not significantly differed with sorghum uptake.…”
Section: Introductionmentioning
confidence: 99%